Impact of Exercise on Cerebrovascular Physiology and Risk of Stroke. Issue 7 (4th May 2022) - Edward, Justin A.; Cornwell, William K.
Abstract : Ischemic heart disease and stroke are the number 1 and number 2 causes of death worldwide, respectively. A lifelong commitment to exercise reduces the risk of these adverse events and is also associated with several cardiometabolic improvements, including reductions in blood pressure, cholesterol, and inflammatory markers, as well as improved glucose control. Routine exercise also reduces the risk of developing comorbidities that increase the risk of cardiovascular or cerebrovascular disease. While the benefits of a lifelong commitment to exercise are well documented, there is a complex interaction between exercise and stroke risk, such that the risk of ischemic or hemorrhagic stroke may increase acutely during or immediately following exercise. In this article, we discuss the physiological responses to different types of exercise, as well as the determinants of resting and exertional cerebrovascular perfusion, and explore the complex interaction between atrial fibrillation, exercise, and stroke risk. Finally, we highlight the increased risk of stroke during different types of exercise, as well as factors that may alleviate this risk.